Adolescent deliveries in rural Cameroon: an 8-year trend, prevalence and adverse maternofoetal outcomes - Valirie Ndip Agbor; Clarence Mvalo Mbanga; Tsi Njim (BMC, 2017)
Abstract Background Adolescent deliveries remain a global public health concern especially in low- and middle-income countries where 95% of these deliveries occur. In Cameroon, adolescent pregnancies have a high disease burden due to their association with adverse pregnancy outcomes. We sought to evaluate the prevalence, trend and adverse maternofoetal outcomes of adolescent deliveries in a rural community in Cameroon. Method We carried out a retrospective register analysis of 1803 singleton deliveries in two health facilities located in the Oku sub-division over an 8-year period (2009 to 2016). We excluded: records without maternal age, babies born before arrival, birthweights less than 1000 g, multiple deliveries and deliveries before 28 weeks gestation. Data analysis was done using Epi info 7.0.8.3. The Fisher's exact test was used to compare categorical variables, while the chi-square test for trends was used to determine time trends. P-values below 5% were considered statistically significant. Results The 8-year prevalence of adolescent deliveries was 20.4% (95% CI = 18.6-22.4) with a significant, downward trend between 2009 and 2016 (P trend = 0.05). Second-fourth degree perineal tears were more likely to complicate adolescent (Age < 20 years) deliveries compared with their adult (Age ≥ 20 years) counterparts (OR = 2.9; 95% CI = 1.8-4.7; p < 0.001). Also, babies born to adolescent mothers were more likely to have a low birthweight (OR = 1.7; 95% CI = 1.1-2.6; p = 0.009) and be asphyxiated at the fifth minute of life (OR = 3.2; 95% CI = 1.9-5.5; p < 0.001). Over an eight-year period, the downward trend in the prevalence of adolescent deliveries was associated with a significant decrease in the trend of neonatal asphyxia at the fifth minute. Married adolescents and their babies were as likely to develop the complications of adolescent delivery such as second-fourth degree perineal tears (OR = 0.8; 95% CI = 0.4-1.6; p = 0.456), low birthweight (OR = 2.1; 95% CI = 0.9-4.7; p = 0.070) and fifth minute neonatal asphyxia (OR = 0.9; 95% CI = 0.4-2.0; p = 0.832) as single adolescents and their babies. Conclusion The prevalence of adolescent deliveries in this rural community is high with one of every five babies born to an adolescent mother. Despite the downward trend indicating a decrease in adolescent deliveries, our study demonstrates the need to reinforce and effectively apply existing government-based public health programme to target key indicators of adolescent pregnancy in Cameroon.